2019
DOI: 10.3746/pnf.2019.24.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Passion Fruit Juice Supplementation on Cardiac Autonomic Function and Blood Glucose in Healthy Subjects

Abstract: Ascorbic acid supplementation provides beneficial effects on enhancing cardiac autonomic function in patients with heart failure. Ascorbic acid also reduces blood sugar levels and enhances insulin activity, and encourages cardiac autonomic function. Passion fruit is rich in ascorbic acid and potential antioxidants. This study aimed to evaluate the acute effects of passion fruit juice (PFJ) supplementation primarily on cardiac autonomic function and secondary on blood glucose in healthy subjects. A randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…Moreover, significant changes in nutritional and functional compounds were usually reported for fruit products after thermal PT. For example, vitamin C is the relevant nutrient in yellow passion fruit within a range of 0.16–0.20 g/kg [ 11 ], which is thermoplastic and easily degraded after thermal PT. It was also reported that vitamin C in kiwifruit was significantly reduced by 38.39% after thermal treatment (110 °C/8.6 s) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, significant changes in nutritional and functional compounds were usually reported for fruit products after thermal PT. For example, vitamin C is the relevant nutrient in yellow passion fruit within a range of 0.16–0.20 g/kg [ 11 ], which is thermoplastic and easily degraded after thermal PT. It was also reported that vitamin C in kiwifruit was significantly reduced by 38.39% after thermal treatment (110 °C/8.6 s) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also called passion flower or egg fruit because it contains apple, guava, banana, strawberry, mango, pineapple, and 130 other kinds of fruit aroma [2,3]. The peel and pulp of passion fruit have many biological functions, such as controlling blood sugar [4], anti-hypertension [5,6], anti-inflammation and reducing fat [7], protecting liver and kidney [8], and regulating cardiac autonomic nerve functions [9]. In addition, passion fruit peel powder can be used as food raw material when added to baking products [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently some clinical studies have been published in the literature that use only 10 participants for measuring postprandial glycemic response [ 59 , 60 , 61 , 62 ]. Additionally, due to its convenience in application for the participants, a glucometer was used in most of these studies [ 28 , 29 , 30 , 31 , 32 ]. In addition, it was reported that the use of a glucometer for monitoring the postprandial blood glucose level has an acceptable sensitivity [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was a single-blind controlled study. The study consisted of three experimental trials (two test meals and one reference) carried out on three different occasions in accordance with the literature [ 28 , 29 , 30 , 31 , 32 ]. We allowed a one-week wash out period between each visit.…”
Section: Methodsmentioning
confidence: 99%